Determining Third- and Fourth-Party Logistics Services Based on Green Supply Chain Management Using Cross-Efficiency and Multi-Criteria Decision Making - Azizi, Kamyar; Shafiee, Morteza; Hajiha, Ali; Saleh, Hilda (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: The purpose of this study was to determine third- and fourth-party logistics services based on green supply chain management, using cross-efficiency and multi-criteria decision making.Methods and Materials: In this study, Interpretive Structural Modeling (ISM) was employed, and certain companies from the Rasht Industrial City were selected for the analysis. The opinions of 10 experts were used both qualitatively and quantitatively. Influential indices were identified using the fuzzy Delphi technique, and the indices were weighted through the fuzzy analytic hierarchy process.Findings: The results of the evaluation of sustainable third- and fourth-party logistics service providers were obtained using the SuperDecisions method. Finally, key components influencing the establishment of 3PL and 4PL companies in the construction industry were identified as economic, environmental, and social factors. In terms of priority and importance, the economic index (with an average weight of 0.485) was ranked first, followed by the environmental index (weight of 0.350), and lastly, the social index (average weight of 0.181). Furthermore, it was found that five companies, A1 to A5, were identified as large companies, with company A3 having the highest sustainability score and company A4 the lowest performance in sustainability.Conclusion: Ultimately, it was determined that for any organization aiming to achieve an effective and sustainable supply chain, the most suitable logistics service providers in the supply chain will be third- and fourth-party logistics providers.